Relationship Between 17-Hydroxyprogesterone Responses to Human Chorionic Gonadotropin and Markers of Ovarian Follicle Morphology in Women With Polycystic Ovary Syndrome - Maas, Kevin H.; Chuan, Sandy S.; Cook-Andersen, Heidi; Su, H. Irene; Duleba, A.; Chang, R. Jeffrey (The journal of clinical endocrinology and metabolism, 2015)
Context:Women with polycystic ovary syndrome (PCOS) have increased 17-hydroxyprogesterone (17-OHP) responses to gonadotropin stimulation although individual variability is substantial, as reflected by exaggerated as well as normal responses. The relationship between 17-OHP responses to gonadotropin stimulation and markers of ovarian function has not been assessed.Objective:To determine whether 17-OHP responses are associated with antral follicle count (AFC), anti-Mullerian hormone (AMH), or inhibin B (Inh B) levels in PCOS and normal women.Design:Prospective study.Setting:Research center at an academic medical center.Participants:Women with PCOS (n = 18) and normal controls (n = 18).Interventions:Blood samples were obtained before and 24 hours after administration of 25 μg recombinant-human chorionic gonadotropin. Ovarian imaging was conducted with three-dimensional pelvic ultrasound.Main Outcome Measures:Basal and stimulated levels of 17-OHP, androgens, estrogen, AMH, Inh B, and AFC.Results:In women with PCOS, 17-OHP responses were heterogeneous and inversely correlated with AMH and Inh B levels, but not AFC. In a subgroup of PCOS women with exaggerated 17-OHP responses, AMH levels were equivalent to that of normal women. In PCOS women with normal 17-OHP responses, AMH levels were markedly elevated.Conclusion:Based on heterogeneous 17-OHP responses to human chorionic gonadotropin in women with PCOS, AMH levels are inversely linked to ovarian androgen production while positively correlated with AFC. These findings suggest that in PCOS, AMH production may reflect redistribution of the follicle population or regulation by intraovarian mechanisms.